Strain-dependent regulation of hippocampal long-term potentiation by dopamine D1/D5 receptors in mice - Hagena, Hardy; Stacho, Martin; Laja, Arthur; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2022)
The magnitude and persistency of long-term potentiation (LTP) in the rodent hippocampus is species-dependent: rats express more robust and more prolonged LTP in response to a broader afferent frequency range than mice. The C57Bl/6 mouse is an extremely popular murine strain used in studies of hippocampal synaptic plasticity and spatial learning. Recently it was reported that it expresses impoverished LTP compared to other murine strains. Given the important role of the dopamine D1/D5 receptor (D1/D5R) in the maintenance of LTP and in memory consolidation, we explored to what extent strain-dependent differences in LTP in mice is determined by differences in D1/D5R-control. In CaOlaHsd mice, robust LTP was induced that lasted for over 24h and which was significantly greater in magnitude than LTP induced in C57Bl/6 mice. Intracerebral treatment with a D1/D5R-antagonist (SCH23390) prevented both the early and late phase of LTP in CaOlaHsd mice, whereas only late-LTP was impaired in C57Bl/6 mice. Treatment with a D1/D5R-agonist (Chloro-PB) facilitated short-term potentiation (STP) into LTP (>24h) in both strains, whereby effects became evident earlier in CaOlaHsd compared to C57Bl/6 mice. Immunohistochemical analysis revealed a significantly higher expression of D1-receptors in the stratum lacunosum moleculare of CaOlaHsd compared to C57Bl/6 mice. These findings highlight differences in D1/D5R- dependent regulation of strain-dependent differences in hippocampal LTP in C57Bl/6 and CaOlaHsd mice, that may be mediated, in part, by differences in the expression of D1R in the hippocampus